2016
DOI: 10.1038/eye.2016.25
|View full text |Cite
|
Sign up to set email alerts
|

Glaucoma detection with damato multifixation campimetry online

Abstract: Purpose To evaluate Damato Multifixation Campimetry Online (DMCO), a free-of-charge internet-based visual field test. DMCO exists in three versions: DMCO BASIC, DMCO STANDARD, and DMCO ADVANCED. The main focus was (i) to investigate the sensitivity and the specificity of the existing DMCO versions in the detection of glaucomatous visual field loss and (ii) to define and evaluate algorithms for the interpretation of DMCO results. Methods The study design was an evaluation of a diagnostic test and included 97 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(35 citation statements)
references
References 33 publications
2
33
0
Order By: Relevance
“…When MD was used as reference, the results revealed that DMCO correctly identified the homonymous quadrantanopia with a sensitivity and specificity of 72.7 and 96.3%, respectively ( Table 2 ). In comparison, the previous results with DMCO had a sensitivity of 64.2% and a specificity of 98.1% [7] . Since the chosen MD value ≤ 6 dB accounts for moderate glaucoma and since MD fails to differentiate between generalized depression and focal defects, we included a second reference standard specially made to fit this specific population.…”
Section: Main Findingsmentioning
confidence: 84%
See 4 more Smart Citations
“…When MD was used as reference, the results revealed that DMCO correctly identified the homonymous quadrantanopia with a sensitivity and specificity of 72.7 and 96.3%, respectively ( Table 2 ). In comparison, the previous results with DMCO had a sensitivity of 64.2% and a specificity of 98.1% [7] . Since the chosen MD value ≤ 6 dB accounts for moderate glaucoma and since MD fails to differentiate between generalized depression and focal defects, we included a second reference standard specially made to fit this specific population.…”
Section: Main Findingsmentioning
confidence: 84%
“…In the repeated test, 5 missed points in the same eye was considered abnormal, and the patient was defined as having definite visual field defects. The prespecified algorithm named "DMCO STANDARD 4,5" sums up the above explanation [7] .…”
Section: Dmcomentioning
confidence: 99%
See 3 more Smart Citations